Split-dose vs same-day reduced-volume polyethylene glycol electrolyte lavage solution for morning colonoscopy - Chan, WK; Azmi, N; Mahadeva, S; Goh, KL (Baishideng Publishing Group Inc, 2024)
AIM: To compare same-day whole-dose vs split-dose of 2-litre polyethylene glycol electrolyte lavage solution (PEG-ELS) plus bisacodyl for colon cleansing for morning colonoscopy. METHODS: Consecutive adult patients undergoing morning colonoscopy were allocated into two groups i.e., same-day whole-dose or split-dose of 2-litre PEG-ELS. Investigators and endoscopists were blinded to the allocation. All patients completed a questionnaire that was designed by Aronchick and colleagues to assess the tolerability of the bowel preparation regime used. In addition, patients answered an ordinal five-value Likert scale question on comfort level during bowel preparation. Endoscopists graded the quality of bowel preparation using the Boston bowel preparation scale (BBPS). In addition, endoscopists gave an overall grading of the quality of bowel preparation. Cecal intubation time, withdrawal time, total colonoscopy time, adenoma detection rate and number of adenomas detected for each patient were recorded. Sample size was calculated using an online calculator for binary outcome non-inferiority trial. Analyses was based upon intent-to-treat. Significance was assumed at P-value < 0.05. RESULTS: Data for 295 patients were analysed. Mean age was 62.0 +/- 14.4 years old and consisted of 50.2 % male. There were 143 and 152 patients in the split-dose and whole-dose group, respectively. Split-dose was as good as whole-dose for quality of bowel preparation. The total BBPS score was as good in the split-dose group compared to the whole-dose group [6 (6-8) vs 6 (6-7), P = 0.038]. There was no difference in cecal intubation rate, cecal intubation time, withdrawal time, total colonoscopy time and adenoma detection rate. Median number of adenoma detected was marginally higher in the split-dose group [2 (1-3) vs 1 (1-2), P = 0.010]. Patients in the whole-dose group had more nausea (37.5% vs 25.2%, P = 0.023) and vomiting (16.4% vs 8.4%, P = 0.037), and were less likely to complete the bowel preparation (94.1% vs 99.3%, P = 0.020). Patients in the split-dose group were less likely to refuse the same bowel preparation regime (6.3% vs 13.8%, P = 0.033) and less likely to want to try another bowel preparation regime (53.8% vs 78.9%, P < 0.001). CONCLUSION: Splitting reduced-volume PEG-ELS for morning colonoscopy is as effective as taking the whole dose on the same morning but is better tolerated and preferred by patients. (C) 2014 Baishideng Publishing Group Inc. All rights reserved.